Osteochondral Autologous Transplantation Compared to Microfracture for Treating Osteochondral Defect: An Updated Meta-analysis of Randomized Controlled Trials - Haien, Zhao; Jiachang, Wu; Qiang, Li; Yufeng, Mei; Zhenwei, Ji (The Journal of Knee Surgery, 2018)
Various techniques have proven to be effective for treating articular cartilage defect of the knee joint, but knowledge regarding which method is best still remains uncertain. Osteochondral autologous transplantation (OAT) provides hyaline or hyaline-like repair for articular defects, whereas microfracture (MF) provides fibrocartilage repair tissue. To compare the OAT with MF procedure for the treatment of articular cartilage defect, we present an update of previous meta-analysis of randomized controlled trials.We searched for the published results of relevant trials. Then, we pooled the outcome measures of the included trials for analysis. The outcome measures assessed in this study included the number of patients who reached excellent or good results, the patients returning to the activity, the International Cartilage Repair Society (ICRS) scores, the failure rate, and the osteoarthritis rate. Six studies and 294 patients were identified as eligible for data extraction and meta-analysis. The pooled result showed that there was no significant difference in the excellent or good results (relative risks [RRs], 1.27; 95% confidence intervals [CIs], 0.95 to 1.70; p = 0.11) and the rate of osteoarthritis (RRs, 0.64; 95% CIs, 0.37 to 1.13; p = 0.12). There were significant differences between the two groups in the scores of ICRS (mean differences [MDs], 12.51; 95% CIs, 10.55 to 14.47; p = 0.00001), the patients returning to activity (RRs, 2.04; 95% CIs, 1.36 to 3.07; p = 0.0006), and in the failure rate (RRs, 0.23; 95% CIs, 0.11 to 0.49; p = 0.0001). OAT has more advantages compared with MF procedure in referring to the index of return to activity, the scores of ICRS, and the rate of failure. However, the limitations restrict the generalizability of this study, and larger, sufficiently powered studies are necessary to evaluate the efficiency of OAT compared with MF procedure in the future.
Keywords: osteochondral autologous transplantation; microfracture; hyaline cartilage; articular cartilage